Biodiesel fuels : science, technology, health, and environment - Konur, Ozcan ([Place of publication not identified] : CRC Press, 2021)
This first volume of the Handbook of Biodiesel and Petrodiesel Fuels presents a representative sample of the population papers in the field of biodiesel fuels in general. PartI provides an overview of the research field on both biodiesel and petrodiesel fuels highlighting primary and secondary research fronts in these fields. PartII presents a representative sample of the population papers in the field of biooils covering major research fronts. The research on the biooils is a fundamental part of the research on the biodiesel fuels. The research in this field has intensified in recent years with the application of advanced catalytic technologies and nanotechnologies in both production and upgrading of biooils. It covers pyrolysis, hydrothermal liquefaction, and upgrading, and characterization and properties of biooils besides an overview of the research field. PartIII presents a representative sample of the population papers in the field of biodiesel fuels in general covering major research fronts. The research in this field has progressed in the lines of production, properties, and emissions of biodiesel fuels. As in the case of biooils, catalysts and additives play a crucial role for the biodiesel fuels. It covers biomass-based catalyst-assisted biodiesel production, enzymatic biodiesel production, additives in biodiesel production, properties, characterization, performance, and policies of biodiesel fuels besides an overview of the research field. PartIV presents a representative sample of the population papers in the field of glycerol, biodiesel waste, covering major research fronts. The research in this field has intensified in recent years with the increasing volume of biodiesel fuels, creating eco-friendly solutions for these wastes of biodiesel fuels for producing valuable biofuels and biochemicals from glycerol. It covers biohydrogen and propanediol production from glycerol as a case study for bioenergy and biochemicals, respectively. This book will be useful to academics and professionals in the fields of Energy Fuels, Chemical Engineering, Physical Chemistry, Biotechnology and Applied Microbiology, Environmental Sciences, and Thermodynamics. Ozcan Konur is both a materials scientist and social scientist by training. He has published around 200 journal papers, book chapters, and conference papers. He has focused on the bioenergy and biofuels in recent years. In 2018, he edited Bioenergy and Biofuels,which brought together the work of over 30 experts in their respective field. He also edited the Handbook of Algal Science, Technology, and Medicine with a strong section on the algal biofuels in 2020.
Part 1: Biodiesel and Petrodiesel Fuels: Science, Technology, Health, and Environment. 1. Biodiesel and petrodiesel fuels: Science, technology, health, and environment. Ozcan Konur2. Biodiesel and petrodiesel fuels: A scientometric review of the research. Ozcan Konur3. Biodiesel and petrodiesel fuels: A review of the research. Ozcan Konur4. Nanotechnology applications in the diesel fuels and the related research fields: A review of the research. Ozcan KonurPart 2: Biooils. 5. Biooils: A scientometric review of the research. Ozcan Konur6. Characterization and properties of biooils: A review of the research. Ozcan Konur7. Biomass pyrolysis and pyrolysis oils: A review of the research Ozcan Konur8. An overview of catalytic bio-oil upgrading. PartI: Processing aqueous-phase compounds. Yong Wang, Jianghao Zhang, Junming Sun9. An overview of catalytic bio-oil upgrading. PartII: Processing oil-phase compounds and real bio-oil. Yong Wang, Jianghao Zhang, Junming Sun10. Bio-oil production through hydrothermal liquefaction (HTL) of biomass: Recent development and future prospects. Shicheng Zhang, Leichang Cao, Daniel C.W. TsangPart 3: Biodiesel fuels in general. 11. Biodiesel fuels: A scientometric review of the research. Yie Hua Tan, Celine Ming Hui Goh, Jibrail Kansedo, N.M. Mubarak, Mohd Lokman Ibrahim12. Biomass-based catalyst-assisted biodiesel production. Yie Hua Tan, Celine Ming Hui Goh, Jibrail Kansedo, N.M. Mubarak, Mohd Lokman Ibrahim13. Enzymatic biodiesel production: challenges and future perspectives. Denise M. G. Freire, Erika C. G. Aguieiras, Eliane P. Cipolatti, Martina C. C. Pinto, Jaqueline G. Duarte, Evelin Andrade Manoel, Jaqueline G. Duarte14. Biodiesel additives: status and perspectives. Mukul Tomar, Lakhan Kumar, Hansham Deval, Navneeta Bharadvaja, Naveen Kumar15. Qualitative characterization of biodiesel fuels : Basics and beyond. Niraj Kumar, Md. Abul Kalam16. Use of biodiesel fuels in the diesel engines. Anh Tuan Hoang, Xuan Phuong Nguyen, Van Viet Pham17. Biodiesel promotion policies: A global perspective. Shashi Kumar Jain, Sunil Kumar, A. ChaubePart 4: Glycerol. 18. Glycerol: A scientometric review of the research. Ozcan Konur19. Hydrogen-rich syngas production from Biodiesel-derived glycerol: An overview of the modeling and optimization strategies.Bamidele Victor Ayodele, Siti Indati Mustapa, May Ali Alsaffa20. Propanediol production from glycerol: A review of the researchOzcan Konur
OCLC-licensed vendor bibliographic record.
Keywords: Biodiesel fuels; MEDICAL / Biotechnology; SCIENCE / Biotechnology